Complement blockade with eculizumab for treatment of severe Coronavirus Disease 2019 in pregnancy: A case series. (12th May 2022) - Burwick, Richard M.; Dellapiana, Gabriela; Newman, Rachel A.; Smithson, Sarah D.; Naqvi, Mariam; Williams, John; Wong, Melissa S.; Bautista, Martha; Gaden, Anna; Kazani, Shamsah D.; Dunn, Derek A.; Ma, Mark H.; et al.
Abstract: Problem: We evaluated eculizumab, a complement protein C5 inhibitor, for treatment of severe COVID‐19 in pregnant and postpartum individuals. Method of Study: Protocol ECU‐COV‐401 (clinicaltrials.gov NCT04355494) is an open label, multicenter, Expanded Access Program (EAP), evaluating eculizumab for treatment of severe COVID‐19. Participants enrolled at our center from August 2020 to February 2021. Hospitalized patients were eligible if they had severe COVID‐19 with bilateral pulmonary infiltrates and oxygen requirement. Eculizumab was administered on day 1 (1200 mg IV) with additional doses if still hospitalized (1200 mg IV on Days 4 and 8; 900 mg IV on Days 15 and 22; optional doses on Days 12 and 18). The primary outcome was survival at Day 15. Secondary outcomes included survival at Day 29, need for mechanical ventilation, and duration of hospital stay. We evaluated pharmacokinetic and pharmacodynamic data, safety, and adverse outcomes. Results: Eight participants were enrolled at the Cedars‐Sinai Medical Center, six during pregnancy (mean 30 ± 4.0 weeks) and two in the postpartum period. Baseline oxygen requirement ranged from 2 L/min nasal cannula to 12 L/min by non‐rebreather mask. The median number of doses of eculizumab was 2 (range 1–3); the median time to hospital discharge was 5.5 days (range 3–12). All participants met the primary outcome of survival at Day 15, and all were alive and free of mechanical ventilation at Day 29. In three participants we demonstrated that free C5 and soluble C5b‐9 levels decreased following treatment. There were no serious adverse maternal or neonatal events attributed to eculizumab at 3 months. Conclusion: We describe use of eculizumab to treat severe COVID‐19 in a small series of pregnant and postpartum adults. A larger, controlled study in pregnancy is indicated.